Jika Pertumbuhan Sektor Unggulan Maksimal, Berapakah Pertumbuhan Ekonomi? - Febrayanto, Catur Raharjo (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2023)
Economic growth, which was contracted due to the Covid-19 pandemic, is gradually starting to pick up again. Almost all business sector sectors will experience an increase in GRDP growth in 2022. The study has conducted in Brebes Regency that has the highest poverty level in Central Java. This study aims to project the economic growth of Brebes Regency in 2023 and 2024 under conditions of maximum GRDP growth in leading sectors that have a high contribution. The data used in this research is secondary data from BPS. The analysis used is the Auto Regressive Integrated Moving Average (ARIMA) using eviews software. Brebes Regency's economic growth is projected to reach 5.61 in 2023 and 6.00 in 2024.